2020
DOI: 10.1590/1519-6984.218915
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical quality of and Escherichia coli resistance profiles in urban surface waters

Abstract: Aquatic ecosystems of urban rivers are contaminated through waste disposal, which poses a public health problem. The objective of this research was to evaluate the quality of water used for recreation and public supply of six rivers in the city of Cascavel - Paraná, including Cascavel, Quati, Bezerra, Antas, Clarito and Amambay. Samples were collected every 4 months in 2017, and their physicochemical and microbiological parameters, as well as resistance profiles of strains of Escherichia coli to antimicrobials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
3
1
1
Order By: Relevance
“…Kumar et al (2020); who evaluate the occurrence of bacteria resistant to antibiotics, the antibiotic-resistant gene, and the concentration of metal in the river of Sri Lanka; show that: for older antibiotics, the percentage of resistance of E. coli is higher than for other antibiotics. In our study, the resistance for E. coliis higher than those obtained by 19 who showed that the highest levels of antibiotic resistance in urban surface waters in Brazil for E. coli, were obtained for ampicillin with 27.7%, tetracycline with 27.7% and amoxicillin with 24.0%.The low or absence of resistance of bacteria to Trimethoprim-Sulfamide may indicate that in all seasons the river has been contaminated with low levels of Trimethoprim-Sulfamide, and indicates low use ofTrimethoprim-Sulfamideby human activity in Bamako. 20 The municipal and industrial wastewater discharge into the Niger river water in Bamako can favorize the presence of residual antibiotics and antibiotic contamination in the river water.…”
Section: Susceptibility Of Isolated Bacterial Pathogens To Antibioticscontrasting
confidence: 64%
“…Kumar et al (2020); who evaluate the occurrence of bacteria resistant to antibiotics, the antibiotic-resistant gene, and the concentration of metal in the river of Sri Lanka; show that: for older antibiotics, the percentage of resistance of E. coli is higher than for other antibiotics. In our study, the resistance for E. coliis higher than those obtained by 19 who showed that the highest levels of antibiotic resistance in urban surface waters in Brazil for E. coli, were obtained for ampicillin with 27.7%, tetracycline with 27.7% and amoxicillin with 24.0%.The low or absence of resistance of bacteria to Trimethoprim-Sulfamide may indicate that in all seasons the river has been contaminated with low levels of Trimethoprim-Sulfamide, and indicates low use ofTrimethoprim-Sulfamideby human activity in Bamako. 20 The municipal and industrial wastewater discharge into the Niger river water in Bamako can favorize the presence of residual antibiotics and antibiotic contamination in the river water.…”
Section: Susceptibility Of Isolated Bacterial Pathogens To Antibioticscontrasting
confidence: 64%
“…The Table 1 shows the results obtained for the physical-chemical parameters evaluated for the urban source of Buritis Lake water; the experiments were done in triplicate. * MAV: maximum allowed value; ** uH: Hazen unit (mg Pt-Co/L); (1) = recommended value; *** NR = not regulated; (2) = true color.…”
Section: Physico-chemical Characterization Of Different Watermentioning
confidence: 99%
“…In many cases, park springs are important resources that are used for water supply in many communities. Anthropogenic actions in natural environments have altered the natural water cycle, impairing soil infiltration and groundwater replacement, thus causing springs to lose their quantitative and qualitative capacities [2].…”
Section: Introductionmentioning
confidence: 99%
“…In rural areas, both human and animal feces may contribute to microbiota modification and, therefore, to the selection of resistant species 7 , 10 . In urban areas, high population density around waterbodies and lack of adequate sanitation influence the degree of contamination 4 , 11 . A previous study 1 demonstrated that the human fecal content in CL was similar to that of raw sewage in Cleveland, Ohio, USA, using tracking of microbial source and DNA of human-indicative Bacteroides species.…”
Section: Discussionmentioning
confidence: 99%